2006
DOI: 10.1175/jcli3748.1
|View full text |Cite
|
Sign up to set email alerts
|

Last Glacial Maximum and Holocene Climate in CCSM3

Abstract: The climate sensitivity of CCSM3 is studied for two past climate forcings, the Last Glacial Maximum (LGM) and the mid-Holocene. The LGM, approximately 21,000 years ago, is a glacial period with large changes in the greenhouse gases, sea level, and ice sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

59
401
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(465 citation statements)
references
References 61 publications
59
401
4
1
Order By: Relevance
“…Coupled LGM climate simulations using the Community Climate System Model (CCSM)1.4 and CCSM3 show a strongly increased abyssal stratification and shallower NADW (7,23,24). Consistent with the results discussed here, these changes have been attributed to enhanced sea-ice export around Antarctica (7) and ultimately reduced CO2 concentrations (8).…”
Section: Discussionsupporting
confidence: 81%
“…Coupled LGM climate simulations using the Community Climate System Model (CCSM)1.4 and CCSM3 show a strongly increased abyssal stratification and shallower NADW (7,23,24). Consistent with the results discussed here, these changes have been attributed to enhanced sea-ice export around Antarctica (7) and ultimately reduced CO2 concentrations (8).…”
Section: Discussionsupporting
confidence: 81%
“…The classical 'linear' model links ENSO variability with the zonal gradient through the 'destabilizing' effect of cold thermocline waters of the Eastern Pacific but produced the opposite relationship [10][11][12] (for example, positive instead of negative correlation) compared with the results of our study. Another mechanism linking ENSO variability and SST zonal gradient is based on external forcing of one of several feedbacks within the ENSO system during a particular season 13,14 .…”
Section: Discussioncontrasting
confidence: 66%
“…Pendleton et al (2015) suggested that early deglaciation in the Brooks Range may have also been related to the impact that the expanded Laurentide Ice Sheet had on atmospheric circulation. Indeed, simulations by global climate models show that the Laurentide Ice Sheet caused significant warming and drying in the Alaska-Yukon region during the LGM (Roe and Lindzen, 2001;Otto-Bliesner et al, 2006), which agrees with very little LGM temperature depressions based on chironomids (Kurek et al, 2009) and pollen (Bartlein et al, 2011). Regardless, among the eight sites in Alaska reviewed here that have sufficient existing chronology to address this question, data from seven sites support significant glacier recession prior to ~18 ka.…”
Section: How Did the Timing Of Glacier Recession Relate To Buildup Ofsupporting
confidence: 67%